DNA barcoding and molecular phylogeny of indigenous bacteria in fishes from a tropical tidal river in Malaysia - Rahman, Mohammad Mustafizur; Izuddin, Mohd Haikal; Khan, Najmus Sakib; John, Akbar; Naim, Mohd Azrul (Springer, 2020)
DNA barcoding along with molecular phylogeny can be used for taxonomic identification, characterization, discovery of species and understanding molecular relationships especially in terms of species divergence. Thus, they facilitate biodiversity studies. Some studies have addressed DNA barcoding of bacterial samples from various sources. Unfortunately, the DNA barcoding of fish bacterial diversity has not been studied especially in the tropical tidal river. Therefore, a study was conducted to (1) identify the observed bacterial isolates by comparing the partial sequence from an unknown sample to a collection of sequences from known reference samples, (2) know the taxonomic and phylogenetic identity of identified bacteria in fish and (3) know the abundance of fish bacteria in the Kuantan River. For this study, three commercially important fish namely Pristipomoides filamentosus, Cyclocheilichthys apogon and Labiobarbus festivus were captured with gill nets from the Kuantan River, Malaysia. Bacteria from skin, gill and gut in fish were cultured at 35 oC for 24 h in both nutrient and marine agar. Bacterial DNA was extracted using a Bacterial Genomic DNA Isolation Kit following manufacturer’s specifications. Isolated DNA was quantified in NanoDrop 2000v and gel eluded in 1.5% agarose gel and visualized under a gel visualizer. PCR products were outsource sequenced at First BASE Laboratories Sdn Bhd using an ABI sequencer by the Sanger sequencing method. Sequences were trimmed using sequence scanner 2.0 V. The aligned sequences were inspected by the eye and edited to remove ambiguities based on PHRED scores and the chromatogram. Fully aligned sequences were subjected to BLAST for nucleotide similarity search against 16S rRNA database. The best matched species were selected based on BLAST results and the lowest genetic distance between the known and unknown nucleotides. Genetic distances (sequence divergences) were calculated using the K2P (Kimura two parameter) distance model. Neighbour-joining (NJ) trees of K2P distances were created to provide a graphic representation of the patterning of divergence between species. This method identified a total of 11 fish bacteria, which are taxonomically classified into Enterobacteriales, Pseudomonadales, Actinomycetales and Bacillales. The range of pairwise genetic distances between species of Enterobacteriales was lower than Bacillales. Similarly, the within group mean genetic distance of Enterobacteriales (0.010) was lower than that of Bacillales (0.055). These results indicate that the identified bacterial species under Enterobacteriales are more closely related than the bacteria species under Bacillales. The mean genetic distances between groups were genetically almost equally close, which was confirmed by the overall mean diversity. Out of 11 species, 7 were identified as Cyclocheilichthys apogon, 8 as Labiobarbus festivus and 7 as Pristipomoides filamentosus. The overall mean bacterial abundance (CFU/g) was higher in C. apogon (6.68 x 103) compared to those in L. festivus (5.12 x 103) and P. filamentosus (5.20 x 103). Overall, the highest bacterial abundances were observed in fish gut (6.62 x 103), followed by fish gill (5.78 x 103) and fish skin (4.60 x 103).